Electrical Properties in Large Frequency and Temperature Ranges of Sr 0.6 Ca0.4TiO3 Ceramics - H. Ait Laasri; A. Tachafine; D. Fasquelle; N. Tentillier; M. Elaatmani; L. C. Costa; J. -C. Carru (Jordan Journal of Physics, 2025)
Lead-free Sr0.6Ca0.4TiO3(SCT) ceramic was prepared by the solid state reaction route. X-Ray diffraction technique showed the phase purity and identified the orthorhombic perovskite structure of the material. Scanning Electronic Microscopy observation evidenced homogeneous morphology and dense microstructure for the ceramic. The dielectric and conductivity properties of the sample were studied using complex impedance measurement technique in a wide range of frequencies and temperatures: from 100 Hz to 1.8 GHz and from 25°C to 550°C. The ceramic exhibits a stable dielectric permittivity and low dielectric losses in frequency and temperature up to 200°C. This is very interesting in view of developing high-quality lead-free ceramic capacitors for applications requiring high temperatures; for example, in cars. The increase in dielectric permittivity for temperatures higher than 200°C may be related to oxygen vacancies that are heat-activated in the material. Dielectric losses show the existence of a dielectric relaxation at low temperatures and low frequencies. Conductivity measurement investigated at high temperatures show on one hand high AC conductivity values attributed to the high temperature jumping process and on the other hand two electrical conductivity mechanisms above 400° C in the material. Keywords: Strontium calcium titanate, Ceramic, Structure, Dielectric properties, Conductivity.